Guidebooks in the context of the development of knowledge about art in the ‘Polish lands’ of the 19th century - Ziarkowski, Dominik (Turyzm/Tourism, 2019)
Former guidebooks are an important category of historical source that allows for the reconstruction of many aspects of the history of tourism. The dynamic development of guidebook literature began in the 19th century when a modern type with descriptions according to routes and containing much practical information was developed. The guidebooks also presented a lot of other information of a general nature, such as geography, ethnology, natural science, as well as descriptions of monuments and works of art. The importance of Polish guidebooks for writing about art is very high yet underestimated. The aim of this paper is to define the role that these publications played in the field of artistic historiography, and to indicate the relationships between the guidebooks and the development of academic research on art. These problems are undoubtedly an interesting area of interdisciplinary relation between the historical development of tourism and academia, with a particular focus on art history in this case.